Government accountability within infrastructure public–private partnerships - Wu, J.; Liu, Henry; Jin, X.; Sing, M. (Pergamon, 2016)
Public–private partnerships (PPPs) have been widely used to deliver infrastructure projects. However, PPPs are being plagued with controversy as some of them were subjected to project overruns and/or poor operations. An underlying issue contributing to unsatisfactory performance of PPPs was a result of an ambiguous accountability of the government. Despite this, limited empirical research has been undertaken to identify the government's accountability within PPPs. Thus, a conceptual framework of the accountability of the government of PPPs is developed in this paper and then examined by conducting a case study of a Chinese PPP project. The findings indicate that the government's accountability in PPPs should shift to enhance the effectiveness of quality services and the efficiency of use of public resources for asset end-users and general population. This paper provides the governments embarking on PPPs with an insight into their accountability, ensuring Value for Money is delivered.